Simulation Based Exploration of SKC Block Cipher Algorithm - Wilson, S; Fred, A. Lenin (International Journal of Computer Sciences and Engineering, 2018)
Video based Face Recognition (VFR) has significantly more challenges when compared to Still Image-based Face Recognition (SIFR). The objective of this paper is to identify faces in video more precisely. In this paper, the minute details of the face are identified by block based technique. It is classified using neural network. The proposed method is tested with four publicly available datasets: Multiple Biometric Grand Challenge (MBGC), Face and Ocular Challenge Series (FOCS), Honda/UCSD and UMD Comcast10 datasets. The proposed method achieves higher recognition rate when compared to other recent methods.